The annual reproductive cycle of Cordylus polyzonus (Reptilia : Cordylidae), with special reference to seasonal changes in steroid hormones - Flemming, A. F.(Alexander Frederik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1988.